Bitcoin Mining Technology - BHASKAR, Nirupama Devi (Institutional Knowledge at Singapore Management University, 2015)
Bitcoin network functions on cryptographic technology and thrives on mining, an incentivized technique to generate new bitcoins. In this chapter, we describe the fundamentals of Bitcoin system, underlying technical aspects of the network and mining process. We have also assessed the methods of mining, the concerned opportunities and implications for the benefit of potential miners. Furthermore, we have also provided a comparison of existing mining pools, different types of pool reward schemes, and the recent innovations in the Bitcoin industry.